Impact of acquired del(17p) in multiple myeloma - Lakshman, Arjun; Painuly, Utkarsh; Rajkumar, S Vincent; Ketterling, Rhett P; Kapoor, Prashant; Greipp, Patricia T; Dispenzieri, Angela; Gertz, Morie A; Buadi, Francis K; Lacy, Martha Q; Dingli, David; Fonder, Amie L; et al. (Blood advances, 2019)
The high-risk abnormality del(17p) can be detected by fluorescence in situ hybridization on malignant plasma cells (PCs) and has an adverse prognostic impact in patients with multiple myeloma (MM). Patients with del(17p) have reduced overall survival (OS). Patients who acquire del(17p) later during the disease course are not well described. The disease characteristics at diagnosis predicting for acquired del(17p) and its overall impact on patient survival is not known. We compared 76 patients with MM who were negative for del(17p) at diagnosis and acquired it later with 152 control MM patients who did not acquire del(17p) at a comparable time point. Patients acquired del(17p) at a median of 35.6 months (range, 4.6-116.1 months) from diagnosis of MM after a median of 2 lines of therapy (range, 1-10 lines of therapy). When compared with controls, patients with acquired del(17p) had shorter median progression-free survival (PFS) (30.1 vs 23.0 months; P = .032) and OS (106.1 vs 68.2 months; P < .001) from diagnosis. After the detection of del(17p), the median PFS was 5.4 months and the median OS was 18.1 months. High lactate dehydrogenase level (odds ratio [OR], 3.69; 95% confidence interval [CI], 1.11-12.24) and presence of t(4;14) (OR, 2.66; 95% CI, 1.09-6.48) or any high-risk translocation (OR, 2.23; 95% CI, 1.00-4.95) at diagnosis predicted acquisition of del(17p). High PC proliferative rate predicted shorter OS from detection of del(17p) (hazard ratio, 2.28; 95% CI, 1.31-3.96; P = .004). Our study shows that acquisition of del(17p) is an important molecular event associated with reduction in OS in MM. Certain baseline factors may predict acquisition of del(17p). This needs validation in prospective data sets.
Keywords: chromozomální delece; genetické asociační studie; Male; Genetic Predisposition to Disease; hybridizace in situ fluorescenční; Genetic Association Studies; prognóza; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; lidské chromozomy, pár 17; Multiple Myeloma; Chromosomes, Human, Pair 17; senioři nad 80 let; lidé; ženské pohlaví; studie případů a kontrol; Biomarkers, Tumor; Humans; Aged, 80 and over; Prognosis; In Situ Hybridization, Fluorescence; mnohočetný myelom; Female; lidé středního věku; Chromosome Deletion; nádorové biomarkery; genetická predispozice k nemoci; Middle Aged